Waitangi Day Address 1996 - Durie, Edward (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: Waitangi Day; mātauranga māori; social life and customs; tiriti o waitangi/treaty of waitangi; tāngata whenua

New Zealand’s Waitangi Day divided? Support for national Day predicts in-group and out-group warmth for Pākehā but only in-group warmth for Māori - Matika, Correna M.; Houkamau, Carla A.; Sibley, Chris G. (International Journal of Intercultural Relations, 2021)
Waitangi Day, New Zealand’s official national day, is often claimed as contentious by commentators and academics. However, research analysing the wider population’s opinions about Waitangi Day are lacking. We address this with two studies using national probability data from the New Zealand Attitudes and Values Study. Most participants supported (51%), rather than opposed (8%), Waitangi Day as a national celebration of biculturalism. Study one indicated that, on average, Pākehā (N = 12390) who opposed Waitangi Day as a bicultural celebration expressed warmer attitudes towards Pākehā but colder attitudes towards Māori. Conversely, support for Waitangi Day as a bicultural celebration among Māori (N = 1928) was, on average, related to warmth towards Māori but uncorrelated with warmth towards Pākehā. Study two assessed whether socio-political attitudes changed in the weeks leading up to, during, and immediately following Waitangi Day in 2015. Contrary to narratives of divisiveness, we failed to detect reliable change in the attitudes of Māori (N = 556) and Pākehā (N = 3203) around Waitangi Day. These findings are inconsistent with anecdotal claims that Waitangi Day may be divisive.
Keywords: Waitangi Day; commemoration; national day; tiriti o waitangi/treaty of waitangi